Rhodium-catalyzed C–H activation/annulation of amidines with 4-diazoisochroman-3-imines toward isochromeno[3, 4-c]isoquinolines. Issue 36 (9th September 2019) - Xu, Shengbo; Qiao, Shanshan; Sun, Song; Yu, Jin-Tao; Cheng, Jiang
Abstract : Rhodium-catalyzed C–H activation/annulation of amidines with 4-diazoisochroman-3-imines toward 8-amino-5 H -isochromeno[3, 4- c ]isoquinolines with good functional group tolerance. Abstract : A rhodium-catalyzed C–H activation/annulation of amidines with 4-diazoisochroman-3-imines has been established to afford a series of 8-amino-5 H -isochromeno[3, 4- c ]isoquinolines in moderate to good yields with good functional group tolerance. This reaction proceeded in a sequential C–H activation/carbene migration insertion/intramolecular annulation procedure and featured the construction of a C–C and C–N bond in one pot. UV-vis and fluorescence spectral analyses of these highly fused heteroarenes were performed.